Intercalation crystallization of phase-pure α-HC(NH2)2PbI3 upon microstructurally engineered PbI2 thin films for planar perovskite solar cells. Issue 12 (9th November 2015) - Zhou, Yuanyuan; Yang, Mengjin; Kwun, Joonsuh; Game, Onkar S.; Zhao, Yixin; Pang, Shuping; Padture, Nitin P.; Zhu, Kai
Abstract : A microstructurally engineered PbI2 thin film with porosity and low crystallinity facilitates the formation of a phase-pure HC(NH2 )2 PbI3 perovskite thin film. Abstract : The microstructure of the solid-PbI2 precursor thin film plays an important role in the intercalation crystallization of the formamidinium lead triiodide perovskite (α-HC(NH2 )2 PbI3 ). It is shown that microstructurally engineered PbI2 thin films with porosity and low crystallinity are the most favorable for conversion into uniform-coverage, phase-pure α-HC(NH2 )2 PbI3 perovskite thin films. Planar perovskite solar cells fabricated using these thin films deliver power conversion efficiency (PCE) up to 13.8%.